Automated imaging system for determine percentage of broken rice - Azizun, Asmat (2011)
Automated Imaging System for Determine Percentage of Broken Rice project is focusing on analyzing the method of determination of broken rice and to develop a prototype of imaging system for determines the percentage of broken rice referring to the conventional method. Broken rice is rice that broke into another pieces that make it smaller than other normal rice.It is due to many aspect such as milling process,the drying process and so many more. This will reduce the quality of rice produced.Hence this Automated System for Determine Percentage of Broken Rice Prototype developed to control the quality of rice that produced which is focused on broken rice.In the result of the project this prototype will show the percentage of broken rice that being measured so that the user can control the process of producing the rice from paddy so that less broken rice are produced and high quality of rice will be delivered to consumer.According to the testing results, this system has met its objectives whereby system able to identify the percentage of broken rice similar to the conventional method with the precision of 98.00%.